Drivers of regional crop variability in Chad. (April 2020) - Nilsson, Erik; Uvo, Cintia Bertacchi; Becker, Per; Persson, Magnus
Highlights: Combines environmental and livelihood data to analyze regional crop production in Chad. Structural breaks are identified and used to detrend the crop statistics. Combines quantitative and qualitative research methods. Advances the explanatory capacity to regional crop variability. Identifies notably differences in explanatory capacities between regions.